Brain Abscess Masquerading as Brain Infarction - Da-Eun Jeong; Jun Lee (Brain Sciences, 2020)
Occasionally, acute ischemic stroke can be difficult to differentiate from acute intracranial infection. We describe a patient who presented with sudden onset of right hemiparesis and fever. Magnetic resonance imaging (MRI) was consistent with an acute stroke, showing multiple lesions with restricted diffusion in the left middle cerebral artery territory. These lesions were not enhancing and were not associated with vasogenic edema. A diagnosis of acute stroke was made based on the clinical and radiographic data. Follow-up MRI obtained eleven days later showed interval development of ring enhancement and vasogenic edema surrounding the previously noted core of restricted diffusion. Based on these findings, the diagnosis was revised to cerebral abscesses and the patient was treated successfully with antibiotics. In retrospect, the largest diffusion-weighted lesion on baseline MRI demonstrated two characteristics that were atypical for stroke: it had an ovoid shape and a subtle T2 hypointense core. This case demonstrates that acute clinical and radiographic presentation of cerebral abscess and ischemic stroke can be strikingly similar. Follow-up imaging can be instrumental in arriving at an accurate diagnosis.